2016
DOI: 10.1002/jcb.25518
|View full text |Cite
|
Sign up to set email alerts
|

CAV1 Prevents Gallbladder Cholesterol Crystallization by Regulating Biosynthesis and Transport of Bile Salts

Abstract: Cholesterol gallstone disease (CGD) is a hepatobiliary disorder which results from a biochemical imbalance in the gallbladder bile. Here we show that loss of CAV1 sensitized mice to lithogenic diet-induced gallbladder cholesterol crystallization, which was associated with dysregulation of several hepatic transporters that efflux cholesterol, phospholipids, and bile salts. The combined effect of increased biliary cholesterol concentration and decreased biliary bile salt secretion in CAV1(-/-) mice led to an inc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 44 publications
0
7
0
Order By: Relevance
“…For drug treatment, ezetimibe (EZE, 5 mg/kg, oral dosing, once a day) was given 1 week prior to the beginning of the LD or HFCD. Ezetimibe is a drug with limited water solubility, thus the components of the HFCD or LD diet were thoroughly mixed with ezetimibe during diet preparation and the bacon-flavoured dough pills were produced by Double Lion CO., LTD (Suzhou,China) for the oral administration of ezetimibe [ 8 ]. The recombinant FGF15 (100 μg/kg/day, Abcam ab206457; Trumpington, UK) or highly selective covalent FGFR4 inhibitor H3B-6527 [ 22 ] (1702259–66-2, 5 mg/kg/day, once a day, i.p.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…For drug treatment, ezetimibe (EZE, 5 mg/kg, oral dosing, once a day) was given 1 week prior to the beginning of the LD or HFCD. Ezetimibe is a drug with limited water solubility, thus the components of the HFCD or LD diet were thoroughly mixed with ezetimibe during diet preparation and the bacon-flavoured dough pills were produced by Double Lion CO., LTD (Suzhou,China) for the oral administration of ezetimibe [ 8 ]. The recombinant FGF15 (100 μg/kg/day, Abcam ab206457; Trumpington, UK) or highly selective covalent FGFR4 inhibitor H3B-6527 [ 22 ] (1702259–66-2, 5 mg/kg/day, once a day, i.p.…”
Section: Methodsmentioning
confidence: 99%
“…Niemann-Pick C1-like 1 (NPC1L1) is a polytopic transmembrane protein that contain a sterol-sensing domain, essential to promote the ability to absorb cholesterol [ 4 , 5 ]. As an inhibitor of NPC1L1 [ 6 ], ezetimibe (EZE) can effectively lower the plasma LDL-cholesterol [ 7 ] and decrease the risk of CGD, as shown in the previous study [ 8 ]. In contrast to rodent NPC1L1, human NPC1L1 is highly expressed in the liver [ 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…CAV1 can also be detected in endosomes, lipid droplets, mitochondria, endoplasmic reticulum, and other intracellular compartments, suggesting that CAV1 may act in a caveolae-independent manner in the liver [ 3 ]. CAV1 is thought to play a key role in cholesterol gallstone disease (CGD), nonalcoholic fatty liver disease (NAFLD), and other diseases associated with high cholesterol levels [ 2 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…Although the exact molecular mechanism remains unclear, excessive accumulation of biliary cholesterol and abnormal cholesterol nucleation time (NT) are considered relevant factors for CGD development [ 7 ]. In the murine CGD model, we observed an increase in the secretion of biliary cholesterol, a decrease in the synthesis of bile acids, and an increase in the bile cholesterol saturation index (CSI)[ 6 ]. Using CAV1 knockout mice can significantly increase the incidence of CGD after 4 weeks of a lithogenetic diet [ 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…Other risk factors for cholesterol gallstones include age, gender, genetics, obesity, weight loss, and bowel disease (7). The association between serum lipid levels and gallstone has been reported and studies have shown that cholesterol saturation index (CSI), which is one of the main factors for gallstone formation, was more crucial than cholesterol concentration (8,9). CSI is described as the ratio of measured concentration of cholesterol to the measured concentration of bile salts plus phospholipid (10).…”
Section: Introductionmentioning
confidence: 99%